2022
DOI: 10.1002/jia2.25944
|View full text |Cite
|
Sign up to set email alerts
|

Availability and experiences of differentiated antiretroviral therapy delivery at HIV care facilities in rural Zimbabwe: a mixed‐method study

Abstract: Introduction Zimbabwe adopted differentiated HIV care policies in 2015 to promote client‐centred care and relieve strain on health facilities. We examined the availability, experiences and perceptions of differentiated antiretroviral therapy (ART) delivery in rural Zimbabwe following the policy adoption. Methods We undertook a cross‐sectional mixed methods study in all the 26 facilities providing HIV care in a rural district in Zimbabwe. We collected quantitative data about ART delivery and visit durations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Although most responses were positive in terms of working conditions, a minority of respondents in all three countries stated that the introduction of DSD models reduced their job satisfaction, due mainly to additional administrative duties and lack of human and nancial resources at their facilities. This was more commonly reported by South African respondents and mirrors ndings from studies in Zimbabwe (34) and Eswatini (31), in which providers reported that having to ll prescriptions for community-based models added to their job burdens.…”
Section: Discussionmentioning
confidence: 55%
“…Although most responses were positive in terms of working conditions, a minority of respondents in all three countries stated that the introduction of DSD models reduced their job satisfaction, due mainly to additional administrative duties and lack of human and nancial resources at their facilities. This was more commonly reported by South African respondents and mirrors ndings from studies in Zimbabwe (34) and Eswatini (31), in which providers reported that having to ll prescriptions for community-based models added to their job burdens.…”
Section: Discussionmentioning
confidence: 55%
“…RoC in both locations were concerned with privacy and the potential for stigma, making a deliberate choice to remain in their care location to avoid HIV-related stigma. While DSD is scaling up, frequently to community settings, previous studies suggest fear of unintended disclosure as a barrier to uptake of community-based DSD models [5,6,8,11,12,26]. In our study, some clinic-based RoC compromised travel and time concerns to receive care at LT, rather than in the community, to avoid being seen receiving HIV-related services.…”
Section: Discussionmentioning
confidence: 68%
“…Recent qualitative studies explored RoC and provider experiences in HIV care with DSDs. RoC in community-based models reported that fewer clinic visits reduce their clinic wait times and transportation costs [57], increase peer support [8,9] and improve treatment adherence [10]. By contrast, clinic-based RoC in SSA reported preferring clinic-based care to community-based refill options because the clinics were near work [5] or they feared stigma and discrimination of inadvertent disclosure of their HIV status if they collected ART at a community venue [5,6,8,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations